Micromorphological study of Centaurea L. (Asteraceae); some taxa of eight sections analysed with scanning electron microscopy and light microscopy - Baser, Birol; Hayta, Sukru; Dogan, Gulden; Celik, Sezgin; Aksoy, Huseyin (SPRINGER, 2019)
This study deals with the pollen morphological characterization of 36 taxa (Sections; Cheirolepis 3, Cynaroides 14, Rhizocalathium 5, Grossheimia 3, Chartolepis 3, Pseudophaeopappus 1, Plumosipappus 1 and Phaeopappus 6) belonging to the genus Centaurea. Pollen slides were prepared using the Acetolysis technique. Light Microscope examination showed pollen grains to be tricolporate, isopolar, radially symmetrical, oblate-spheroidal, prolate-spheroidal, subprolate, tectum perforate and scabrate. We identified two basic types of pollen grains, designated type I (Scabrate), type II (Microechinate). 34 taxa evaluated resemble Wagenitz's Jacea pollen type and 2 taxa Montana pollen type. We present micrographs of pollen grains, together with descriptions of the characteristics of their structure. We found that the pollen characters (shape, exine structure, sculpturing) were useful for classification.
Keywords: Asteraceae; Centaurea; LM; Pollen morphology; SEM; GENERAL COEFFICIENT; COMPOSITAE; CARDUEAE; TURKEY; SIMILARITY; PALYNOLOGY; Life Sciences & Biomedicine - Other Topics